Community-engaged and Implementation Science-informed Pediatric Sleep Intervention Research. - Williamson, Ariel A.; Levenson, Jessica C. (Current Sleep Medicine Reports, 2026)
Purpose of Review: Community-engaged research (CEnR) and implementation science can address gaps in translating evidence-based interventions to real-world practice by considering the needs of patients/families, clinicians, and contexts. This review summarizes recent pediatric sleep intervention research that incorporates CEnR and/or implementation science principles. We also identify key areas for future research. Recent Findings: Most reviewed studies incorporated CEnR methods during intervention development, adaptation, and/or pilot testing. Studies with community members collaborating in named research team roles were rare. Although some studies evaluated intervention acceptability, feasibility, and fidelity, very few used established implementation science theories, models, or frameworks, and even fewer focused on developing and testing implementation strategies. Summary: It is critical to establish sleep researcher-community partnerships that promote community empowerment and capacity-building, and to conduct implementation strategy research. We encourage researchers to further integrate CEnR and implementation science to advance pediatric sleep health and address the many gaps in care.